1991
DOI: 10.1093/brain/114.2.1045
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Multiple Sclerosis: A Geographically Based Study

Abstract: A multivariate hierarchical analysis was used to assess the significance of several demographic and clinical factors in multiple sclerosis patients. We used the time to reach level 6 on the disability status scale (DSS) of Kurtzke as endpoint. Several factors at presentation were significantly associated with an adverse outcome including older age at onset, male sex, cerebellar involvement or insidious onset of a motor deficit as first symptom. Factors ascertained later which were associated significantly with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(87 citation statements)
references
References 0 publications
3
81
0
3
Order By: Relevance
“…On the other hand, male gender, older age at onset, PP onset and onset with motor LT dysfunction or a combination of symptoms were associated with relatively more severe disease and shorter time to disability. These results are in agreement with previous studies [5,6,17]. It should be noted, however, that the present findings have methodological limitations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, male gender, older age at onset, PP onset and onset with motor LT dysfunction or a combination of symptoms were associated with relatively more severe disease and shorter time to disability. These results are in agreement with previous studies [5,6,17]. It should be noted, however, that the present findings have methodological limitations.…”
Section: Discussionsupporting
confidence: 93%
“…We have provided detailed information regarding presenting symptomatology in this subgroup, given the relative scarcity of such data in the recent literature. We have also attempted to verify demographic and clinical variables at onset known to influence prognosis from previous studies [5,6,17]. …”
Section: Introductionmentioning
confidence: 99%
“…In most studies, it has been found that less than 10% of all patients have late-onset MS (LOMS), defined as disease onset on or after age 50 [1]. Although LOMS is considered to be associated with adverse prognosis [2,3,4,5], whether it has any prognostic relevance independent of primary progressive MS (PPMS), an established marker of poor prognosis strongly associated with older age at onset, remains a debatable issue [6,7,8,9]. Age at disease onset was an independent predictor of early progression to disability only in relapsing-remitting onset MS (RRMS) but not in PPMS in a cohort of 2,054 patients [10], while older age was independently associated with short time to disability in a cohort of 500 PPMS patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…Gender, age at onset, course at onset, degree of recovery from the first relapse, time to second relapse and the number of relapses in the first years affect the time from onset to EDSS 4 or 6 [21,22]. Male gender, older age at onset and progressive onset MS are predictors of an unfavorable outcome [23]. …”
Section: General Introduction On Multiple Sclerosismentioning
confidence: 99%